Comparison of the prevalence of bacteriocin encoding genes in Lactobacillus spp. isolated from fecal samples of healthy volunteers, IBD-patient and IBD-recovered - Seyedeh Tina Miri; Fattah Sotoodehnejadnematalahi; Mohammad Mehdi Amiri; Mohammad Reza Pourshafie; Mahdi Rohani (Iranian Journal of Microbiology, 2022)
Background and Objectives: Bacteriocins are antimicrobial peptides produced by many genera of bacteria especially Lactobacillus spp. against many pathogens, adapt bacterial composition in the gut and inhibit dysbiosis that can lead to inflammation disorders like inflammatory bowel disease (IBD). The aim of this study was to compare the prevalence of bacteriocin genes in health, IBD disease and recovery conditions. Materials and Methods: In this survey 115 Lactobacillus spp. from 58 fecal samples of three different groups were evaluated. Comparison of the presence of bacteriocin genes in different groups were assayed by purified samples and PCR method, followed by statistical analysis to identify the effect of inflammation in the proportion of Lactobacillus spp. and presence of their bacteriocin genomes. Results: Of 115 Lactobacillus spp. 60% of samples had positive bacteriocin-encoding genes which included: gassericin-A 29.56%, acidocin 15.65%, plantaricin-NC8 18.26%, plantaricin-S 13.04%, lactacin-F 9.5%, sakacin-P 6.08% and gassericin-T 6.08%. Results indicated that the percentage of positive bacteriocin genes were much more in healthy volunteer and IBD-recovered in comparison to IBD-patients which showed the effect of inflammation in the presence of bacteriocin genes. Conclusion: The results obtained in this study demonstrated that the presence of bacteriocin genes can be related to health and disease states and inflammatory disease affected the prevalence of bacteriocin-encoding genes. This approach can help to identify bacterial functions that can be targeted in future concepts of IBD therapy.